Factores que influyen en el nivel de satisfacción de los agentes del presupuesto participativo de Cercado de Lima, 2022 - Pacheco Moya, José Luis (2022)
The present study was proposed in order to demonstrate that there is a direct and significant relationship between the factors of the participatory budget and the satisfaction of the agents of the participatory budget of Cercado de Lima, in the year 2022.Methodologically, the study is of quantitative approach, of experimental design in which we worked with a population made up of 35 agents participating in the participatory budgets of the six neighborhood units to which a questionnaire was applied as an instrument which went through processes of reliability. and validity. The data collected and interpreted allowed us to affirm that there is a direct and significant relationship between the factors of the participatory budget and the satisfaction of the agents of the participatory budget of Cercado de Lima, in the year 2022, when the Spearman's Rho correlation coefficient was discovered to be 752**, it was clear that the value of =.000, which is less than 0.05.